(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article explores the strategic imperative of expanding the participation of banks in the capital market as a catalyst for deepening financial intermediation and fostering sustainable economic development. In many emerging and transitioning economies, the capital market remains underutilized by the banking sector, limiting the diversification of funding sources and constraining market liquidity. The study analyzes the institutional, regulatory, and operational barriers that restrict banks’ active involvement in capital market activities such as underwriting, securities issuance, investment banking, and asset management. It further evaluates global best practices where banks play a pivotal role in enhancing capital market infrastructure, supporting public offerings, and promoting financial innovation. Using empirical data and comparative analysis, the research highlights the macroeconomic benefits of broader bank participation, including improved capital allocation, increased investor confidence, and a more resilient financial system. The article concludes with policy recommendations aimed at regulatory reform, institutional capacity building, and the creation of enabling environments that encourage banks to expand their roles beyond traditional lending. These reforms are essential for building an integrated and efficient capital market capable of supporting long-term national development goals.